Exploring the Impact of Communicative Leadership on Employee Engagement: The Mediated Moderated Effect of Employee Perceptions of Communication and Leaders' Intention to use ChatGPT - Kumar, Shalendra S.; Ku, Bonwoo; Sen, Rajit; Kumar, Mahendra; Lata, Ranjani (Journal of Ecohumanism, 2024)
Employee engagement is recognized as an integral part of organizational vitality. Enhancing such engagement is a critical factor for any leader seeking to develop a positive work environment and performance within the organization. The study explores the intricate relationship between communicative leadership and employee engagement, with a focal mediating variable of how employees perceive communication. Building on the technology acceptance model (TAM), which emphasizes perceived usefulness and ease of use, the current study also evaluated the potential moderating impact of leader intention to use ChatGPT between communicative leadership and employee engagement, as well as between communicative leadership and employee’s perception of communication. A survey distributed to public sector employees in Fiji Island yielded a response of 345 participants through cross-sectional and purposive sampling. Structural equation modeling (SEM) was employed to determine the model fit. The findings of the study show that communicative leaders significantly enhance employee engagement through employee's perception of communication. This suggests that when employees perceived leader communication well, they are more likely to engage in collaborative decision-making and demonstrate greater mutual obligation and commitment in the organization. Additionally, by encouraging dialogues, communicative leaders establish a safe environment where employees feel comfortable expressing their voice ensuring they are listened to and valued. Based on TAM factors, the leader’s intention to use ChatGPT partially moderates the relationship. This suggests that having perceived AI technology as user-friendly, leaders could leverage ChatGPT to streamline the flow of communication and provide a real-time solution. Finally, the current study offers both theoretical and practical implications, limitations, and suggestions for research directions.